Pengaruh Laba Per Lembar Saham, Dividen Per Lembar Saham Dan Pengungkit Keuangan Terhadap Harga Saham Perusahaan Otomotif Yang Terdaftar di Bursa Efek Indonesia Periode 2006-2010 - Henny Ritha; Luna Mukti Lestari (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2014)
This study aimed to determine the effect of Earnings Per Share, Dividend Per Share and the Financial Leverage of the company's stock price on auto listed in Indonesia Stock Exchange 2006-2010 period either simultaneously or partially. The method used is the method of documentation, the data processing techniques using the Software Package for Social Sciences (SPSS) version 19.0 for windows evaluation. In conducting this study the authors using multiple linear regression analysis. The results either simultaneously or partially indicates that a significant difference between earnings per share, dividend per share and financial leverage on stock prices. This is evident from the calculated F and t is greater than F table (2.975) and t table (1,706). In addition, 69.3 % stock price able to be explained by the variable earnings per share, dividend per share and financial leverage. The remaining 30.7 % can be explained by other variables, such as Return On Assets (ROA), SBI Interest Rate, Price Earning Ratio (PER). The result is expected to be useful for the researchers themselves, the automotive company's management, as well as potential investors for further research. For automotive company's management should pay attention to earnings per share, dividend per share and the financial leverage that can be used to predict the rise or fall of stock prices is then to take the decision to invest.